KESENJANGAN KAWASAN DAN STRATEGI PEMBANGUNAN LOKAL MENGHADAPI ASEAN ECONOMY COMMUNITY 2015 - Sugiarto Pramono . (SPEKTRUM, 2013)
Abstrct This paper aims to design a local strategy to decrease the economic disparities in Southeast Asia to build a foundation for the ASEAN Economic Community 2015 (AEC 2015). The argument in this paper was prepared on the assumption, that the region's economic liberalization was not accompanied by the readiness of the local economy will produce gaps. Recommendation of this paper was the readiness of the local economy should be priorities in facing the AEC in 2015. Key Words: Asean Economic Commonity, local economy